Religious Phenomena of the Hallstatt Communities of Southern Pannonia - Potrebica, Hrvoje (Array, 2012)
This overview of some religious concepts of the Hallstatt community in the territory of today's Croatia, touched upon some general problems relating to the religious phenomena of the period. First and foremost is the lack of exploration of settlements. Because of this, there are no data on the formal position of the cult within the social structure of the community, which would permit a deeper understanding of the religious phenomena described. The rare information on shrines is insufficient for establishing their general character. The places of cult known to date are mostly local and linked directly to the activities of the community they belong to, sharing all of its specific features. Some of them were used continuously for a long period of time, for example the one by the settlement at Turska Kosa, reflecting the continuity of a stable community in that area. However, it is also possible that these places of cult were an important active factor in the homogeneity of local communities, which helped preserve their integrity during important cultural transformations. None of this excludes the possibility of existence of shrines which were not tied only to one specific community, or whose importance surpassed a community's boundaries. Such shrines could have been places of pilgrimage, that is, the focus of gathering and exchange of spiritual and material culture among individual Hallstatt communities. If these places did exist, it would be very important to identify their special location in relation to the local community – that is, whether they were linked to a specific community and acted as a catalyst of its power, or whether they stood as distinct religious centres. Despite all the local characteristics which reflect the high level of heterogeneity of the Hallstatt Culture, there are still some general features that permit the treatment of Hallstatt religious phenomena as a separate unity. Although manifestations characteristic of that unity, some of which are mentioned in this paper, share some more or less pronounced similarities with Mediterranean, primarily Greek, manifestations, after careful consideration of communication routes in this region, I believe that these similarities are primarily a result of a common 'Indo-European' conceptual heritage, rather than of direct contacts. However, it was this common, conditionally-speaking mythological, heritage that allowed communication between different communities and members of different communities. Certain elements of spiritual culture may have arrived in the Hallstatt region through chain transfer, by the intercession of a line of Iron Age centres and elite groups belonging to them, but the potential of individual mobility should not be forgotten, either.